Pajak Penghasilan pada UMKM Sektor Perdagangan - Restiyanti Restiyanti; Ari Budi Kristanto (Telaah Bisnis, 2016)
AbstractThe research aimed to compare the calculation method of income tax using methods of “pembukuan” and “pencatatan” based on the income tax law (UU PPh) No. 36 year 2008, as well as the calculation method according to the government regulation (PP) No. 46 year 2013, regarding the trade sector of MSMEs. The research data was obtained from questionnaires and interviews directly sent to the owners of the trade sector MSMEs in Kecamatan Tengaran. The sampling method of this research is snowball sampling technique. The tax payable that have been calculated by the respondents were compared to respondents’ nature of the business, commodity type, and business size. The result of this study showed that the tax calculation based on government regulation (PP) No. 46 year 2013 was the method that lead to the most efficient tax payable for the trading business for both retail and distributor for clothing, vegetables and daily needs trading business; and also for small scale trading business. However for micro scale trading businesses, the method of “Pencatatan” was the most efficient method for these respondents group. The research concluded that there was no single method providing results as the most efficient tax payable for all group of respondents. Based on this finding, it can be recommended to the regulator to make the income tax calculation method is as an option instead of rigid regulation, as the background of the regulation is the simplicity to the tax payer (particularly on Government Regulation (PP) No 46 year2013) and in order to achieve the principle of taxation, namely the principle of economic efficiency.